Literatura, ideološkost in imaginarno - Potocco, Marcello (Primerjalna književnost, 2006)
Literature, Ideology and Imaginary. In a literary work, ideology may at most be manifested through a dependant function that does not neccessarily destroy the aesthetic experience. In the literary structure, elements may be found that enable a stronger identification with the extra-textual world, but these are primarily identifications with the significations of the social imaginary.The ideological function of the text is always dependant on standards and codes of interpretation, while ideology interpellates as a social-historical force imposed by the reader on the text.
Keywords: literatura; literature; ideologija; art; umetnost; aesthetics; estetika; literarne študije; imaginarno